The EGFR Pathway Regulates BCRP Expression in NSCLC Cells: Role of Erlotinib - Porcelli, Letizia; Giovannetti, Elisa; G. Assaraf, Yehuda; Jansen, Gerrit; L. Scheffer, George; Kathman, Ietje; Azzariti, Amalia; Paradiso, Angelo; J. Peters, Godefridus (Current Drug Targets, 2014)
While multidrug resistance (MDR) in cancer is well established, little is known about the cellular pathways regulating the expression and trafficking of the MDR efflux transporter like BCRP (ABCG2). Here we evaluated the role of signalling downstream of EGFR on BCRP expression and sub-cellular localization using lung cancer cells harboring BCRP but expressing various EGFR and Ras activating mutations; A549 (K-Ras-G12S), H292 wild-type EGFR and Ras, and H1650 (EGFR-DelE747-A750). Immunocytochemistry and immunofluorescence studies demonstrated that BCRP was predominantly intracellular but its expression was found also on the plasma membrane in A549 and H1650 cells with activated Ras and EGFR. Remarkably, EGFR inhibition by erlotinib at IC50 concentrations induced a differential timedependent alteration in BCRP gene and protein expression. In H1650 cells, erlotinib enhanced both the total and plasma membrane degradation of BCRP by ubiquitination within 6-24 hours, whereas BCRP expression regained the original basal levels after 48 hours. In erlotinib treated H292 cells, BCRP levels decreased at 24 hours until 72 hours, whereas in A549 cells erlotinib initially reduced BCRP expression but then induced its accumulation on the plasma membrane at 72 hours. We further found that the PI3K/Akt inhibitor LY294002 down-regulated BCRP expression, hence showing that the Akt pathway is involved in the regulation of BCRP expression but not in its localization in these lung cancer cell lines. Finally, the selective BCRP transport inhibitor Ko143 did not increase erlotinib sensitivity, but did decrease the transport activity of BCRP in A549 and H1650 cells as it induced the accumulation of its transport substrate topotecan. In conclusion, our results suggest that the EGFR and Akt pathways are involved in regulation of BCRP expression, trafficking and drug transport activity. These findings warrant future studies on the pharmacologic modulation of these pathways to enhance the efficacy of anticancer combinations of erlotinib with drugs that are BCRP transport substrates.
Keywords: mutations